2017
DOI: 10.1177/1747954117746498
|View full text |Cite
|
Sign up to set email alerts
|

Examining prior experiences and career attainment of FBS football head coaches

Abstract: A Football Bowl Subdivision college head coach position is desired in the American football coaching profession due to associated financial benefits, social network improvements, and prestige. The rise of an individual from player, to assistant coach, and eventually head coach, is primarily understood anecdotally. This empirical evaluation of head coaching attainment provided insight into the career progression of these important sport leaders. The purpose of this study was to assess prior experiences (e.g., p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Previous studies have explored the relationship between a coach's alumni status and the length of their tenure, indicating a positive correlation (Johnson et al, 2023;Nesseler et al, 2012;Tracy et al, 2018). However, this study explored nature of coaching change rather than length of tenure and alumni status was found to have predictive value.…”
Section: Other Factorsmentioning
confidence: 72%
See 4 more Smart Citations
“…Previous studies have explored the relationship between a coach's alumni status and the length of their tenure, indicating a positive correlation (Johnson et al, 2023;Nesseler et al, 2012;Tracy et al, 2018). However, this study explored nature of coaching change rather than length of tenure and alumni status was found to have predictive value.…”
Section: Other Factorsmentioning
confidence: 72%
“…Johnson et al (2023) found that alumni status had a significant positive correlation with the length of a coach's tenure in a variety of sports. Similarly, in a study about FBS football assistant coaches, Tracy et al (2018) found that playing and coaching at their alma mater was the strongest predictor of retaining the head coaching position. A coach's alumni status was more predictive than previous winning seasons or playoff experience.…”
Section: Alumnimentioning
confidence: 85%
See 3 more Smart Citations